Substitution of kaolin with coal fly ash as a raw material for the manufacture of cement. - Ranjisi, Tedias (Midlands State University, 2017)
This dissertation investigated the substitution of Kaolin with Coal Fly Ash (CFA) as raw material for the manufacture of cement. The research sought to establish the optimum quantity of CFA, Sand and Limestone required to produce a cement that had improved early day strength and latter strengths of cement due to substitution of kaolin with CFA. This was a novel and creative research where a total of twenty experiments formulated from the central composite design were carried out to investigate the optimum quantities of CFA, Limestone and Sand that is required for the new product. A comprehensive full chemical and physical analysis were carried out under standard conditions to determine the compositions of the raw materials and of the new products formed. From the results that were obtained in this research, CFA and Kaolin chemical analysis showed that it has more aluminium oxide than Kaolin thus it can be used as substitute for kaolin. It was also obtained from the results that CFAplays a major role in the early day strength of cement, with Limestone and Sand playing a major role in the latter day strengths. The optimized results also showed that volumes of CFA of about 32.91% will reach a 2 days’ strength of 40.9431Mpa which are better than 14.0000 Mpa that are obtained when Kaolin is used. From the optimized data, it was seen that CFA volumes of 17.05 to 20.30% will produce 2days’ cement strength that will be around 30 Mpa on strength and if it is incorporated with Limestone volumes of 84.00 to 85.00% and Sand volumes of 8.80 to 8.90% the latter-day strength will be around 39.0000MPa. These strength results are actually greater than the expected strength of OPC according to the ASTM standards. It was also obtained that CFA plays a major role in the setting time, expansion and water consistency of cement but all the observed results were in the ASTM standards and SAZ range.